EFFECT OF MEDICATION RELATED EDUCATIONAL INTERVENTIONS ON IMPROVING MEDICATION ADHERENCE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - George, Nimmy Elizabeth; Sunny, Smrithy; Sam, Anitta Mariyam; Sabu, Aleena Susan; Rodrigues, Prudence A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objectives: To assess the patient medication adherence using 8 item morisky medication adherence scale (MMAS). To categorize patients based on their adherence to antidiabetic medications into low, medium, and high adherent. To provide educational interventions such as patient counseling using teach-back method, patient medication information leaflet, and audio-visual aids and thus to improve the patient medication adherence. Methods: After obtaining informed consent from the patients, data of the patients were recorded in data collection forms. Their adherence to antidiabetic medication was evaluated using 8 item MMAS and patients were categorized into low, medium, and high adherence groups based on the score. Counseling was done based on the categorization (high, medium, and low). During review, again adherence was rechecked using 8 item MMAS. Results: Medication adherence was measured using 8 item MMAS on review and adherence was found to be improved using different patient counseling methods according to their adherence category. Improvement in score within low adherence group was found to be 83.87%; improvement of the low adherence group to medium adherence group was 16.12%. Improvement within the medium adherence group was 82.14% and from medium adherence to high adherence group was 17.85%. Conclusion: Patient counseling can improve adherence in type 2 diabetes mellitus patients, which in turn help patients in achieving optimal glycemic control.